2017
DOI: 10.1590/1678-457x.35416
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of firmness loss in guava cv. Pedro Sato during ripening at room temperature

Abstract: Guava (Psidium guajava L.) is fruit with very short shelf life due to associated with the loss of firmness in the pulp and information on the activity of enzymes that degrade pectic substances, as well as the amount of pectin, is very contradictory and not clearly defined. This work showed that the firmness of the fruit decreased sharply on the first four days of ripening. The identified phenolic compounds had their content increased with fruit maturation. The addition of the enzymes cellulase and hemicellulas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…This is in accord with prior work showing that the content of soluble pectin (i.e. galacturonic acid) increased with a reduction of guava fruits firmness (Braga et al ., 2017). Together, these results indicate that cell wall degradation may also contribute to fruit softening in guava.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in accord with prior work showing that the content of soluble pectin (i.e. galacturonic acid) increased with a reduction of guava fruits firmness (Braga et al ., 2017). Together, these results indicate that cell wall degradation may also contribute to fruit softening in guava.…”
Section: Resultsmentioning
confidence: 99%
“…(2012) and Braga et al . (2017) found that pectin plays an important role in the firmness of guava fruits. Our transcriptomic analysis represents the first investigation of gene expression profiles underlying pathways involved pectin degradation in different tissues and fruit developmental stages in guava.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decline in respiration rate by applying higher doses of CaCl 2 may increase the fruit firmness and rigidity. The cell wall, where pectin polymers are mainly considered responsible for fruit firmness, can present glycosidic chains interconnected by phenolic compounds [34]. These phenolic compounds retarded the respiration rate and ethylene production by slowing down the metabolic activity and prolonging the shelf life of tomato fruits [10].…”
Section: Respiration and Ethylene Productionmentioning
confidence: 99%